Recent Advancements of Treatment for Leptomeningeal Carcinomatosis - Gwak, Ho-Shin (J Korean Neurosurg Soc, 2015)
Treatment of Leptomeningeal carcinomatosis (LMC) from solid cancers has not advanced noticeably since the introduction of intra-cerebrospinal fluid (CSF) chemotherapy in the 1970's. The marginal survival benefit and difficulty of intrathecal chemotherapy injection has hindered its wide spread use. Even after the introduction of intraventricular chemotherapy with Ommaya reservoir, frequent development of CSF flow disturbance, manifested as increased intracranial pressure (ICP), made injected drug to be distributed unevenly and thus, the therapy became ineffective. Systemic chemotherapy for LMC has been limited as effective CSF concentration can hardly be achieved except high dose methotrexate (MTX) intravenous administration. However, the introduction of small molecular weight target inhibitors for primary cancer treatment has changed the old concept of 'blood-brain barrier' as the ultimate barrier to systemically administered drugs. Conventional oral administration achieves an effective concentration at the nanomolar level. Furthermore, many studies report that a combined treatment of target inhibitor and intra-CSF chemotherapy significantly prolongs patient survival. Ventriculolumbar perfusion (VLP) chemotherapy has sought to increase drug delivery to the subarachnoid CSF space even in patients with disturbed CSF flow. Recently authors performed phase 1 and 2 clinical trial of VLP chemotherapy with MTX, and 3/4th of patients with increased ICP got controlled ICP and the survival was prolonged. Further trials are required with newly available drugs for CSF chemotherapy. Additionally, new LMC biologic/pharmacodynamic markers for early diagnosis and monitoring of the treatment response are to be identified with the help of advanced molecular biology techniques.